Teo Estetis Dalam Ritual Tumpek Krulut Pada Masyarakat Bali (Suatu Upaya dalam Mewujudkan Etika Kasih Sayang) - I Wayan Sunampan Putra (Jnanasidanta, 2021)
Hinduism is inseparable from the cultural aspect, between religion and culture can go hand in hand. One of the most visible cultures is art. Art or art in Balinese Hindu society has the most important position. This can be seen from all forms of religious ceremony implementation inseparable from art. Art in Bali is grouped into sacred art and profane art. Art is also inseparable from theological relationships. This can be seen from the concept of gods in the aspect of art. This paper tries to elaborate on the theology of art in krulut tumpek ritual in Balinese society. Where tumpek krulut is a feast of worship kepafda aspect of the Godhead that has conferred kehgran. Tumpek krulut is also a form of moral value that teaches the love of living beings.